Risk of breast cancer in men in relation to weight change: A national case‐control study in England and Wales. Issue 11 (3rd February 2022) - Swerdlow, Anthony J.; Bruce, Cydney; Cooke, Rosie; Coulson, Penny; Schoemaker, Minouk J.; Jones, Michael E.
Abstract: Breast cancer is uncommon in men and knowledge about its causation limited. Obesity is a risk factor but there has been no investigation of whether weight change is an independent risk factor, as it is in women. In a national case‐control study, 1998 men with breast cancer incident in England and Wales during 2005 to 2017 and 1597 male controls were interviewed about risk factors for breast cancer including anthropometric factors at several ages. Relative risks of breast cancer in relation to changes in body mass index (BMI) and waist/height ratios at these ages were obtained by logistic regression modelling. There were significant trends of increasing breast cancer risk with increase in BMI from age 20 to 40 (odds ratio [OR] 1.11 [95% confidence interval (CI) 1.05‐1.17] per 2 kg/m 2 increase in BMI; P < .001), and from age 40 to 60 (OR 1.12 [1.04‐1.20]; P = .003), and with increase in self‐reported adiposity compared to peers at age 11 to BMI compared with peers at age 20 (OR 1.19 [1.09‐1.30]; P < .001). Increase in waist/height ratio from age 20 to 5 years before diagnosis was also highly significantly associated with risk (OR 1.13 [1.08‐1.19]; P < .001). The associations with increases in BMI and waist/height ratio were significant independently of each other and of BMI or waist/height ratio at the start of the period of change analysed, and effects were similar for invasive and in situ tumours separately. Increases in BMI and abdominal obesity are each risk factors for breast cancer in men, independently of obesity per se. These associations might relate to increasing oestrogen levels with weight gain, but this needs investigation. Abstract : What's new? Although obesity is an established risk factor for breast cancer in men, there have been no investigations of whether weight change is an independent risk factor, as it is in women. In an interview case‐control study including 1998 cases and 1597 controls, authors found that increase in body mass index and in abdominal obesity are each significant risk factors for breast cancer in men, independent of obesity per se.